Control of white mold (Sclerotinia sclerotiorum) through plant-mediated RNA interference - Philip L. Walker; Dylan J. Ziegler; Shayna Giesbrecht; Austein McLoughlin; Joey Wan; Deirdre Khan; Vanessa Hoi; Steve Whyard; Mark F. Belmonte (Scientific Reports, 2023)
Abstract The causative agent of white mold, Sclerotinia sclerotiorum, is capable of infecting over 600 plant species and is responsible for significant crop losses across the globe. Control is currently dependent on broad-spectrum chemical agents that can negatively impact the agroecological environment, presenting a need to develop alternative control measures. In this study, we developed transgenic Arabidopsis thaliana (AT1703) expressing hairpin (hp)RNA to silence S. sclerotiorum ABHYDROLASE-3 and slow infection through host induced gene silencing (HIGS). Leaf infection assays show reduced S. sclerotiorum lesion size, fungal load, and ABHYDROLASE-3 transcript abundance in AT1703 compared to wild-type Col-0. To better understand how HIGS influences host–pathogen interactions, we performed global RNA sequencing on AT1703 and wild-type Col-0 directly at the site of S. sclerotiorum infection. RNA sequencing data reveals enrichment of the salicylic acid (SA)-mediated systemic acquired resistance (SAR) pathway, as well as transcription factors predicted to regulate plant immunity. Using RT-qPCR, we identified predicted interacting partners of ABHYDROLASE-3 in the polyamine synthesis pathway of S. sclerotiorum that demonstrate co-reduction with ABHYDROLASE-3 transcript levels during infection. Together, these results demonstrate the utility of HIGS technology in slowing S. sclerotiorum infection and provide insight into the role of ABHYDROLASE-3 in the A. thaliana–S. sclerotiorum pathosystem.